Ecotoxicological profile of a high prevalence marine disease area in Florida's Gulf coast - Manes Costanza; Herren Richard; Kozuch Marianne; Cooper Evan; Lilyestrom Margaret; Evans Daniel; Godfrey David; Duffy David; Capua Ilaria; Carthy Raymond (Marine Pollution Bulletin, 2026)

Wide-ranging migration of post-nesting hawksbill sea turtles (Eretmochelys imbricata) from the Caribbean island of Nevis - Daniel R. Evans; Lemuel Pemberton; Raymond R. Carthy (Marine Biology, 2024)

Coastal Armoring and Sea Turtles: Beachfront Homeowners’ Opinions and Intent - Melissa K. Hill; Martha C. Monroe; Thomas T. Ankersen; Raymond R. Carthy; Tom A. Kay (Coastal Management, 2019)

Migration routes, foraging behavior, and site fidelity of loggerhead sea turtles (Caretta caretta) satellite tracked from a globally important rookery - Daniel R. Evans; Raymond R. Carthy; Simona A. Ceriani (Marine Biology, 2019)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Temporospatial dynamics and public health significance of bacterial flora identified on a major leatherback turtle ( Dermochelys coriacea ) nesting beach in the Southern Caribbean - Ayanna Carla N. Phillips; Johanna Coutou; Stacy Rajh; Neville Stewart; Antonio Watson; Adam Jehu; Hamish Asmath; Francis Dziva; Chandrashekhar Unakal; Ridley Holder; Raymond Raoul Carthy (Marine Ecology, 2017)
Grande Riviere beach, on the island of Trinidad, supports the largest nesting population of leatherback turtles in the Caribbean region. Throughout the nesting season, nests are naturally disturbed by newly nesting females, resulting in egg breakage and loss of some nest viability. This environment is ideal for the growth and proliferation of microorganisms. The range of bacterial flora present in beach sand and egg shells was examined, with emphasis on bacteria that may pose a threat to public and animal health. The extent to which the bacterial load and genera on the beach changed throughout the season was also assessed. Twenty‐five genera were identified, with Pseudomonas spp. found to be the most predominant environmental bacteria. Four genera identified possess zoonotic potential, while five additional genera are known to be of public and animal health significance. Distinct shifts in the density and distribution of bacteria were observed along the beach from early to peak nesting season. Shifts were seen across heavily traversed zones, thus highlighting the potential exposure threats posed to beach visitors and animals alike. Further studies aimed at speciating this population of bacteria, as well as isolating potential fungal pathogens may mitigate this threat. Identification of bacterial agents that are specifically pathogenic to leatherback turtles, turtle eggs, hatchlings and those who may interact with these animals will serve to enhance and guide efforts to better conserve this species and protect the health of all who visit this ecologically significant site.

Erratum to: Estimates of vital rates for a declining loggerhead turtle (Caretta caretta) subpopulation: implications for management - Margaret M. Lamont; I. Fujisaki; Raymond R. Carthy (Marine Biology, 2015)

Estimates of vital rates for a declining loggerhead turtle (Caretta caretta) subpopulation: implications for management - Margaret M. Lamont; I. Fujisaki; Raymond R. Carthy (Marine Biology, 2014)

Winter Diets of Immature Green Turtles (Chelonia mydas) on a Northern Feeding Ground: Integrating Stomach Contents and Stable Isotope Analyses - Natalie C. Williams; Karen A. Bjorndal; Margaret M. Lamont; Raymond R. Carthy (Estuaries and Coasts, 2014)

Temporal, spatial, and body size effects on growth rates of loggerhead sea turtles (Caretta caretta) in the Northwest Atlantic - Karen A. Bjorndal; Barbara A. Schroeder; Allen M. Foley; Blair E. Witherington; Michael Bresette; David Clark; Richard M. Herren; Michael D. Arendt; Jeffrey R. Schmid; Anne B. Meylan; Peter A. Meylan; Jane A. Provancha; et al. (Marine Biology, 2013)

Genetic structure of the southeastern United States loggerhead turtle nesting aggregation: evidence of additional structure within the peninsular Florida recovery unit - Brian M. Shamblin; Mark G. Dodd; Dean A. Bagley; Llewellyn M. Ehrhart; Anton D. Tucker; Chris Johnson; Raymond R. Carthy; Russell A. Scarpino; Erin McMichael; David S. Addison; Kristina L. Williams; Michael G. Frick; et al. (Marine Biology, 2011)

An Owner's Manual for the Chelonioidae - Raymond R. Carthy (Conservation Biology, 2006)